9.4k views
3 votes
Question 7 of 10

In order to solve the following system of equations by addition, which of the
following could you do before adding the equations so that one variable will
be eliminated when you add them? hs
2x – 4y= 5
6x - 3y=10
A. Multiply the top equation by -3 and the bottom equation by 2.
B. Multiply the top equation by 3 and the bottom equation by 4.
o o
C. Multiply the top equation by -2
D. Multiply the top equation by -3.

2 Answers

2 votes

Answer:

The answer is D.

Explanation:

D. Multiply the top equation by -3.

This works because if you multiply the top equation by -3 then it will be

-3(2x – 4y= 5) which is -6x + 12y = -15

now our equation is : -6x +12y = -15

6x - 3y = 10

As you can see we can eliminate -6x and 6x if we add those two equation together.

User Yigal
by
5.6k points
2 votes

Answer:

D. Multiply the top equation by -3.

Explanation:

2x – 4y= 5 -3(2x – 4y= 5) -6x + 12y= -15

6x - 3y=10 6x - 3y=10

No you can eliminate -6 and 6

User Josep Vidal
by
5.3k points